2015
DOI: 10.3324/haematol.2014.117457
|View full text |Cite
|
Sign up to set email alerts
|

The impact of category, cytopathology and cytogenetics on development and progression of clonal and malignant myeloid transformation in inherited bone marrow failure syndromes

Abstract: Apart from challenges in defining IBMFS-associated CMMT, the classification and grading of this disorder presents another challenge, because some of the clinical and biological features that are used to characterize de novo CMMT (e.g. prominent dysplasia and increased marrow cellularity) are less common in IBMFS-associated CMMT. In 2002 we developed the "Category Cytology Cytogenetics" (CCC) classification for pediatric MDS, which aimed to address aspects not only of de novo MDS, but also of therapy-related an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Hypermethylation leads to the silencing of regulatory genes and aberrant cell behavior. Furthermore, hypermethylation of the promoters of various genes, such as p15, 15,16 DLX4, 17 p73, 18 and VTRNA1- 3,19 has been associated with unfavorable prognosis in MDS.…”
Section: Response To Treatment With Azacitidine In Children With Advamentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermethylation leads to the silencing of regulatory genes and aberrant cell behavior. Furthermore, hypermethylation of the promoters of various genes, such as p15, 15,16 DLX4, 17 p73, 18 and VTRNA1- 3,19 has been associated with unfavorable prognosis in MDS.…”
Section: Response To Treatment With Azacitidine In Children With Advamentioning
confidence: 99%
“…All consecutive patients from 1 to 18 years of age who fulfilled the diagnostic criteria of pediatric refractory cytopenia with excess blasts (RCEB) according to the Category Cytology Cytogenetics (CCC) classification of childhood MDS, 3 and were treated, at least partially, at the Hospital for Sick Children, Toronto, Canada between January 1 st 2000 and December 31 st 2015, were identified. The definition of RCEB included the categories of "refractory anemia with excess blasts (RAEB)" and "refractory anemia with excess blasts in transformation (RAEB-T)" as defined by Hasle et al 4 In summary, patients were included if they had bone marrow blast counts of 5-29% in addition to one or more of the following: (i) sustained unexplained cytopenia, (ii) prominent multilineage dysplasia, and (iii) acquired clonal cytogenetic abnormality in hematopoietic cells.…”
Section: Patient Populationmentioning
confidence: 99%
“…The most common abnormality of bone marrow is isochromosome (7)(q10), (i(7q)), which accounts for up to 40% of abnormalities 2. The significance of i(7q) is controversial 7, 8, 9, 10. The present report describes two male siblings with SDS, one that harbored cytogenetic abnormality of i(7q) in bone marrow and required allogeneic HCT.…”
Section: Introductionmentioning
confidence: 83%
“…That report noted that the patient with i(7q) died of progressive cytopenia, whereas the other sibling who was without i(7q) did not have progressive cytopenia. Cada et al 8 suggested that SDS patients who have clones with i(7q) may have progressive bone marrow failure because all of the patients with i(7q) had severe cytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in the choice for an appropriate diagnostic and therapeutic approach. It may be intriguing to note that no significant information links AML to a defined calcium dis-metabolism even if we should remind the sheer differences in the cytogenetic abnormalities observed in FA-AML patients, mostly pediatric patients, in comparison to the adult AML patients [57,58,59] . Furthermore, we should note also that the low [Ca 2+ ] i in FA is expressed as a physiological stretch before a clearly established baseline condition of dysplasia.…”
Section: Implication Of An Altered Calcium Homeostasis In Famentioning
confidence: 99%